2023
DOI: 10.1017/s1049023x23000183
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Public Interest in Cardiopulmonary Resuscitation with Cardiac Arrest Epidemiology and National Socioeconomic Indicators: Exploratory Infodemiology Study

Abstract: Study Objective: Web-based big data analytics provides a great opportunity to measure public interest in cardiac arrest (CA) and cardiopulmonary resuscitation (CPR). This study aimed to examine associations of online interest in CPR and CA with epidemiological characteristics of out-of-hospital CA (OHCA) and national socioeconomic indicators in a set of European countries. Methods: Country-level online search popularity data for CPR and CA topics measured in relative search volume (RSV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The primary data are available online in Mendeley Data repository. 11 Abbreviations: CA, cardiac arrest; CPR, cardiopulmonary resuscitation; RSV, relative search volume; OHCA, out-of-hospital cardiac arrest.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary data are available online in Mendeley Data repository. 11 Abbreviations: CA, cardiac arrest; CPR, cardiopulmonary resuscitation; RSV, relative search volume; OHCA, out-of-hospital cardiac arrest.…”
Section: Resultsmentioning
confidence: 99%
“…The data that support the findings of this study are openly available in Mendeley Data repository. 11…”
Section: Methodsmentioning
confidence: 99%
“…Birkun et al showed that Bing and Bard performed poorly in the scenario of non-breathing victims. The alignment of responses with guideline-consistent instructions was inadequate, with the average percentage of completely satisfactory answers being 9.5% for Bing and 11.4% for Bard (13).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, a study showed that the mean percentage of acceptable answers from Bard (Google LLC; Mountain View, California USA) and Bing in response to the BLS scenario were 11.4 and 9.5%, respectively. These researchers believed that the recommendations of these chatbots ignored some details of the resuscitation instructions, which could potentially harm the victim (13).…”
Section: Introductionmentioning
confidence: 99%